Propensity for selfing varies within a population of hermaphroditic snails: coexistence of selfers, outcrossers and mixed-mating individuals - Anja Felmy; Alena B. Streiff; Jukka Jokela (Royal Society Open Science, 2023)
To understand mating-system evolution in self-compatible hermaphrodites, variation in selfing rates is highly relevant. Empirical studies are rarely designed to capture variation between individuals, instead often comparing species and populations. Yet, evolution primarily occurs within populations, rendering among-individual variation essential. Observed individual selfing rates depend on the environment (e.g. differences in mate availability) and individuals' propensity for selfing. We quantified individual variation in selfing propensity in the snail Radix balthica by conducting laboratory mating trials that manipulated mate availability (low versus moderate) and estimating selfing rates from progeny arrays. We also measured female lifetime fitness. We found substantial among-individual variation in selfing propensity, including pure selfers (32%), pure outcrossers (31%) and mixed-mating individuals that selfed and outcrossed (37%). Experimental levels of mate availability did not significantly affect selfing rates. Selfers had reduced female liftetime fitness. Our results show that the propensity for selfing can differ considerably among individuals, with similar proportions of selfers, outcrossers and mixed maters. As mate availability did not affect selfing, our ‘moderate’ experimental level of mate availability might still have been too low to prompt selfers to outcross. This and the observed fitness differences also cautiously suggest that investigating the heritability of selfing propensities might be worthwhile in this population.